Antimicrobial resistance of Escherichia coli strains isolated from the bursa of Fabricius in broilers - Carvajal B., Edna (2019)
The aim of this study was to determine the percentage of sensitivity or resistance of strains of E. coli isolated from asymptomatic broiler chicken against 18 common antibiotics used in poultry and in human medicine. In addition, strains that produce extended-spectrum beta-lactamases (ESBL) from a farm or slaughterhouses in the poultry area of Santander, Colombia. The circulation of strains resistant to beta-lactams, cephalosporins, aminoglycosides, quinolones and sulfonamides was determined, as well as antibiotics widely used in other non-farm environments. The content of the bursa of Fabricius was cultivated in McConkey agar obtaining 46 strains of E. coli. Susceptibility tests (n=18) were conducted to the isolated strains, and 91% of the strains were resistant to ampicillin and 80% to cephalosporins. The association of antibiotics with beta-lactamase inhibitors (ampicillin sulbactam and amoxicillin / clavulanic acid) showed 30% resistance. The double disc test was used to evaluate the presence of strains of E. coli producing extendedspectrum beta-lactamases (ESBL) confirming its presence in 63% of the samples. Results showed the presence of E. coli strains in asymptomatic chicken broilers with high antimicrobial resistance, including expression of ESBL.